Development and validity of the early clinical assessment of balance for young children with cerebral palsy. (December 2014) - McCoy, Sarah W.; Bartlett, Doreen J.; Yocum, Allison; Jeffries, Lynn; Fiss, Alyssa L.; Chiarello, Lisa; Palisano, Robert J.
Abstract Objectives: Validity of the Early Clinical Assessment of Balance (ECAB), to monitor postural stability in children with cerebral palsy (CP), was evaluated. Methods: 410 children with CP, 1.5 to 5 years old, participated. Physical therapists scored children on the Movement Assessment of Infants Automatic Reactions section and Pediatric Balance Scale. Through consensus, researchers selected items from both measures to create the ECAB. Content and construct validity were examined through item correlations, comparison of ECAB scores among motor ability, age and gender groups and correlations with the Gross Motor Function Measure 66 basal and ceiling (GMFM-66-B&C). Results: Internal consistency was high (Cronbach's alpha = 0.92). ECAB differed significantly among motor ability, children <31 months old scored lower than older children, but there was no difference between boys and girls. ECAB and GMFM-66-B&C scores correlated strongly (r = 0.97). Conclusion: Validity of the ECAB was supported. Reliability and responsiveness need study.